Nurses' Spiritual Competence Towards Spiritual Care and Patient Satisfaction: A Systematic Review - Fadlilah , Nur; Muhith, Abdul; Setiyowati, Eppy (Journal of Applied Nursing and Health, 2024)
Background: Spiritual competence in nursing is essential in providing holistic health services. Nurses are not only responsible for the physical aspects of patients but also psychological, social, and spiritual aspects. Spiritual care is an effort made to meet the spiritual needs of the patient, which includes the moral, emotional, and religious values or beliefs that the patient has. This study aims to systematically review the literature examining the relationship between nurses' spiritual competence, the delivery of spiritual care, and its impact on patient satisfaction levels. Methods: This research method This article employs a systematic review methodology. The literature search was conducted between September and October 2024 using journal databases such as ScienceDirect, PubMed, ClinicalKey, and Google Scholar. Results: A nurse's spiritual competence significantly influences the quality of spiritual care provided to patients. Further research is essential to explore the various dimensions of spirituality in nursing and its impact on patient outcomes. Conclusion: The study highlights the critical role of spiritual competence in delivering effective spiritual care and improving patient satisfaction. Future research should explore the multidimensional aspects of spirituality in nursing and their broader implications for patient outcomes and holistic healthcare practices.